Pedagogical Mediation and Scientific Knowledge Using a Sample of Ninth Grade Science Teachers in Two School Districts of the Costa Rica Educational System for the Development of Scientific Competencies - León-León, Giselle (2019)
This article presents the results of a study conducted within the framework of an interunit project of the National University of Costa Rica (UNA), titled “Las competencias científicas en estudiantes del tercer ciclo (9º) de educación general básica en la Región Central de Heredia circuito 01 y 02” (Zúñiga y León 2017), on scientific competencies and pedagogical mediation. Specifically, this paper focused on the objective of characterizing the pedagogical mediation that teachers use in their daily practice, for the development of scientific competencies in ninth grade students (corresponding to the third cycle of Costa Rican general basic education). The research was based on the naturalist paradigm and a methodology that assumes a type of mixed research design, where qualitative and quantitative data are compared with the use of observation and a questionnaire to achieve a deeper analysis. The research was conducted with the collaboration of 17 science teachers from Heredia School District (the administrative division of school zones proposed by the Ministry of Education of Costa Rica), willing to collaborate; so, to avoid generalizations, the results obtained only apply to that group. Among the main results, it is highlighted that the role, methodology (strategies and resources), educating act, and evaluation used by the teaching group of the third cycle tends to be closer to a traditional teaching model focused on the transmission of knowledge. Likewise, it is evident that, since mediation mainly focuses on the traditional model, conceptual and scientific knowledge is prioritized over procedural and attitudinal one in planning, evaluation, and mediation.